Understanding older Chicanas - Facio, Elisa (SAGE series on race and ethnic relations)
This work explores how older Chicanas cope with being marginalized as poor widows or grandmothers, and obtain the economic and cultural resources they require. It also reviews how scholars and public policy makers have perceived them, and points out the significance of new data regarding social meaning for future policy